2022
DOI: 10.1007/s10900-022-01085-5
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Smoking During Covid-19 Pandemic: Association with Sociodemographic, Behavioral, and Mental Health Characteristics

Abstract: The Covid-19 pandemic is related to increased alcohol consumption and smoking. These behaviors may be related to several sociodemographic, behavioral and mental health factors. Thus, the aim of this study was to assess the association between alcohol consumption and cigarette smoking with sociodemographic, behavioral and mental health characteristics. This study used data from two population-based studies conducted in two cities from Southern Brazil amid the Covid-19 pandemic. Individuals aged 18 years or olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 46 publications
1
18
0
2
Order By: Relevance
“…In addition, those in the 60-69 and 70-79 years age groups had a lower risk of having alcohol use disorder than those in the 18-29 years age group. This is consistent with the findings of a previous study 38 which found an association between male sex and younger age and alcohol consumption during the COVID-19 pandemic.…”
Section: Audsupporting
confidence: 93%
“…In addition, those in the 60-69 and 70-79 years age groups had a lower risk of having alcohol use disorder than those in the 18-29 years age group. This is consistent with the findings of a previous study 38 which found an association between male sex and younger age and alcohol consumption during the COVID-19 pandemic.…”
Section: Audsupporting
confidence: 93%
“…It is thought that individuals with smoking and alcohol addiction will have a higher risk of unhealthy nutrition, and that being in quarantine at home for a long time during the pandemic will trigger these bad habits as a result of the psychological effects. In another study supporting this view, it was reported that cigarette and alcohol consumption increased during the pandemic, the nutritional quality of alcohol users was low and this situation would increase in depressed people (21).…”
Section: Discussionmentioning
confidence: 91%
“…A total of 1,683 individuals were interviewed: 820 from the Health of the Criciúma Population 19,20 study and 863 from the Mental COVID 22,23,24 study (response rate of 86.1% in 2019 and 75% in 2020). In the first study, most of the participants were female (63.8%), older adults (45%), and reported having white skin color (82.5%).…”
Section: Resultsmentioning
confidence: 99%
“…The Mental COVID study 22,23,24 , carried out from October 2020 to January 2021 (during COVID-19 pandemic), included the same target population, that is, individuals aged 18 years or older, living in the urban area of Criciúma. The sampling process of Mental COVID was also conducted in two stages: the first stage, which focused on the random selection of the primary units (the census tracts), and the second stage, when the secondary units (households) were randomly selected.…”
Section: Setting Study Sample and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation